PENERAPAN HUKUM PIDANA ADAT DALAM MASYARAKAT KAMPUNG CIKONDANG - Rahma Ghefyra; Rangga Putrana; Saskia Berthianna; Syifa Nur Syahidah Dharmawan; Syifa Rahmah; Zahrah Nur Afifah; Ende Hasbi Nassaruddin (Cahaya Ilmu Bangsa, 2023)
Jurnal